ANALISA STRUKTUR ABUTMENT UNDERPASS JALAN NASIONAL STA 6+850 PROYEK JALAN TOL RUAS BINJAI – LANGSA SEKSI BINJAI – PANGKALAN BRANDAN - Sihombing, Darwin; Nainggolan, Paulo M; Endayanti, M.; Gultom, A. (Prodi Teknik Sipil Fakultas Teknik Universitas Darma Agung, 2022)
Prestressed concrete bridge STA 6+850 Provincial Road Penggal Binjai-Langsa Freeway is one of the footbridges connecting the fast road from Binjai To Langsa with a total bridge length of 30 meters and a total bridge width of 26.90 meters (2 lanes). Preparation of the prestressed walkway for Provincial Road STA 6+850 Freeway at the Binjai-Langsa joint is based on RSNI-T-02-2005 for loading on the walkway. Based on RSNI-T-02-2005, the loading for the prestressing walkway spans 30 meters with a total of 3 tendons, where one tendon is 19 standards with a diameter of 12.7 millimeters. The tension in the flexural compression fiber due to the influence of prestressing, dead load and live load is 0.45 fci' (13500 kPa). Control of overturning stability in the X and Y directions on the abutment, the number of safety (SF) against overturning is greater than the allowable SF = 2.2 (safe). The carrying capacity of the pile foundation bearing capacity (Qg) was analyzed based on SPT data, the value obtained was 87207.33 kN using Meyerhoff's (1956) method from SPT field data.